Computable general equilibrium analysis: Opening a black box - Christoph Böhringer; Thomas Fox Rutherford; Wolfgang Wiegard (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2003)
Computable general equilibrium models play an important role in applied economic research. These models accommodate the micro-consistent systematic analysis of complex economic problems where analytical solutions are either not available or do not provide adequate information. However, the computational approach to economic policy analysis also has severe shortcomings of its own. In general, scientific publications include a complete listing of neither the algebraic model underlying the numerical simulation nor the data used to calibrate model parameters. Even if the model algebra and the data were fully laid out, replication of results would still require specialized programming skills. As a consequence, CGE analyses are often perceived as a black box to non-expert readers. This article aims at lowering the barriers to numerical CGE analysis along two lines. First, we provide a compact introduction to recent methods of CGE model implementation that may substantially ease entry for potential modelers. Second, and equally important, we illustrate the non-technical access to CGE analysis by means of a user-friendly interface that allows non-modelers to test and develop their economic intuition on general equilibrium interactions without programming skills.
Keywords: 330; equilibrium models; numerical CGE analysis